A Case of Prolonged Cholestatic Hepatitis Induced by Azithromycin in a Young Woman. (11th January 2012) - Maggioli, Caterina; Santi, Luca; Zaccherini, Giacomo; Bevilacqua, Vittoria; Giunchi, Francesca; Caraceni, Paolo
Abstract : Azithromycin, a semisynthetic macrolides, is frequently prescribed for the treatment of middle ear and upper respiratory tract infections, bronchitis, and community-acquired pneumonia. This antibiotic is usually well tolerated, and a rapid resolving cholestatic hepatitis has been described up to now only in six patients all, except one, over 65 years of age. We here report the case of a prolonged cholestatic hepatitis after administration of azithromycin in a young woman with no history of liver disease.